Experimental optimization of compact double-cell stimulated Brillouin scattering pulse compressor - Wang, Hongli; Shan, Shimin; Wang, Gao (Frontiers in Physics, 2023)
To optimize the output of SBS sub-nanosecond pulse compression, two kinds of compact double-cell structures are carried out and compared experimentally. The beam parameters of the compact double-cell structure are calculated theoretically, which provides the selection guidance of structural parameters such as lens focal length and SBS cell size. The dependence of lens parameters and medium parameters on SBS output parameters are experimentally studied. Results show that SBS pulse compression enters the saturation region at a low injection energy with a long focal length lens or a large gain coefficient medium. For compact double-cell setup with one lens, it is easy to obtain narrow pulses for the medium FC40 with a short phonon lifetime. While in setup with two lenses, it is easy to obtain SBS output with a high energy efficiency and narrow pulse width for HT110 medium with a large gain coefficient. The pulse width compression ratio is up to 16 times after optimization. These experimental results can provide references for the experimental design of SBS pulse compression.